Journey to peace : the stable South Asia - Jarg, M. S. (New Delhi : Manas Publications, 2005)
On the political relations between Pakistan and India and interferences by China and USA
Includes index
Keywords: India -- Foreign relations -- Pakistan; Pakistan -- Foreign relations -- India